1999
DOI: 10.1093/oep/51.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Attainment in secondary school

Abstract: This paper studies attainment in secondary schools. We estimate an education production function in which attainment depends upon parental inputs, peer group inputs and schooling inputs. We find that the most powerful parental input is parental interest in children, as assessed by teachers. We find a strong peer group effect. The school pupil-teacher ratio does not enter significantly. The only strongly endogenous variable is initial attainment. We argue that this is due to measurement error. There is some evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 15 publications
10
147
1
6
Order By: Relevance
“…Nguyen and Taylor (2003) show that the effects of parental characteristics are also positive, but differ among ethnic groups and selected tracks for pupils' post-high school choices in the USA. Feinstein and Symons (1999) and Ermisch and Francesconi (2001) support these findings with similar evidence for the UK (see Li 2007 for China, Maani and Kalb 2007 for New Zealand). Chen and Kaplan (1999) concentrate on the relationship between family structure and educational attainment of the child.…”
Section: Introductionsupporting
confidence: 68%
“…Nguyen and Taylor (2003) show that the effects of parental characteristics are also positive, but differ among ethnic groups and selected tracks for pupils' post-high school choices in the USA. Feinstein and Symons (1999) and Ermisch and Francesconi (2001) support these findings with similar evidence for the UK (see Li 2007 for China, Maani and Kalb 2007 for New Zealand). Chen and Kaplan (1999) concentrate on the relationship between family structure and educational attainment of the child.…”
Section: Introductionsupporting
confidence: 68%
“…Within the school, the peer effect can be approximated by combining the average grade of the school, the proportion of children in the class coming from non-manual background, the number of suspended students in the school etc. (Feinstein and Symons, 1999). The concept is similar to the school advantage/disadvantage examined above.…”
Section: School Context and Climatementioning
confidence: 90%
“…In a meta-analysis of 41 studies, Jeynes (2005) found that PI improved academic performance of urban elementary school pupils by 0.7 to 0.75 of a standard deviation, the effect also being significant for children from disadvantaged backgrounds (either by race, ethnicity, or family income). Feinstein and Symons (1999) found that an increase of PI in child's schooling from 0 to 1 (the highest level) would increase the combined test scores by 24.4 percentage points (measured on a scale of 0-100). 5 They found that PI is the most important variable influencing school outcomes.…”
Section: Family Contextmentioning
confidence: 98%
See 2 more Smart Citations